Confirmatory factor analysis of spiritual leadership components in primary school administrators in Thailand - Khanchai Chottantitarasagul; Piangkae Poopayang; Sunan Siphai (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
This study aims to examine the confirmatory factor of spiritual leadership among school administrators under the jurisdiction of the Office of the Basic Education Commission in Thailand. A quantitative research methodology was employed, utilizing Structural Equation Modeling (SEM) to validate the proposed model. The research process included identifying research questions, reviewing theoretical frameworks, developing the model, conducting statistical validation, and interpreting the results. Data were collected from 705 school administrators using structured questionnaires. A confirmatory factor analysis revealed that the proposed model demonstrated an excellent fit with the empirical data. The model fit indices met all conventional thresholds: Chi-square=0.146, degrees of freedom (df)=1, p-value=0.703, Chi-square/df=0.146 ( 2), Adjusted Goodness of Fit Index (AGFI)=0.999, Comparative Fit Index (CFI)= .000, Normed Fit Index (NFI)=1.000, Residual Mean Square (RMR)=0.001, and Root Mean Square Error of Approximation (RMSEA)=0.000. Analysis of the standardized factor loadings presented that the indicator vision had the highest loading value (0.79), indicating its primary role in embodying spiritual leadership, followed by trust (0.66), Hope (0.65), and faith (0.59). All indicators had loading values above the 0.50 threshold, confirming the convergent validity of the model. These findings validate the construct of spiritual leadership as comprising 4 key dimensions and affirm the model’s structural soundness for theoretical study and practical application in educational leadership.